Facile morphological control of fluorescent nano/microstructures via self-assembly and phase separation of trigonal azobenzenes showing aggregation-induced emission enhancement in polymer matrices. Issue 16 (28th April 2015) - Han, Mina; Takeoka, Yukikazu; Seki, Takahiro
<x xml:space="preserve">Abstract</x> We report a facile strategy for constructing diverse nano/microstructured morphologies via self-assembly and phase separation of trigonal azobenzene chromophores showing AIEE in polymer matrices.